Bioenergetic and Reproductive Plantations of True Poplar Species in the Central Black Earth Region of Russia - Anatoly P. Tsarev; Raisa P. Tsareva; Vadim A. Tsarev; Petr M. Evlakov (Лесной журнал, 2023)
The need to use fast-growing tree for bioenergy production was noted in the international and domestic press in the second half of the 20th century. In the first twenty years of the current century in a number of countries this problem has not only acquired research character, but also found a practical solution. The results of the research of true poplars (black, balsamic and their hybrids) on newly established field experiments in the Central Black Earth Region of the Russian Federation are considered. The aim of the research is to study and select promising forms of true poplars. Two types of experimental plots were established: variety testing plots and collection-stool bed plantations for reproduction of promising clones and varieties. The rooting ability, safety and growth in height were monitored on variety testing plots, and the yield of planting material (stem cuttings) was determined on reproductive collection-stool bed plantations. The best results on growth were noted on 2-year variety testing site facilities of LLC "United Nurseries" and carbon polygon of Voronezh State Forestry University named after G.F. Morozov in Voronezh region. Several fast-growing clones and varieties of true poplars at juvenile age were identified here. Among them we can mention P. trichocarpa No. 84, euramerican cultivar Sacrau-59, hybrids E.s.-38, and Version. Their average heights ranged from 359±21.5 to 416±12.7 cm, and maximum heights ranged from 435 to 495 cm. The best results in growing reproductive material were obtained at the collection-stool bed plantation of the Kulikovsky Forestry of the Lipetsk Forestry Department. Among annual plants the best growth results were found in the poplars trichocarpa No. 84 (183 cm), deltoides (149 cm), Marylandica (147 cm), simonii (133 cm) and E.s.-38 (157 cm). Among the annual shoots grown on three-year-old roots, Sacrau-59 (340 cm), E.s.-38 and deltoides (240 cm each), Marilandica' (230 cm) and Version (200 cm) were superior to the others in height. In general, the yield of standard stem cuttings from annual plants on 1-year-old roots was about 16 thousand pieces/ha and from annual plants on 3-year-old roots – 78 460 pieces/ ha. The clones and varieties mentioned above can be recommended for creation of bioenergy plantations in the Central Black Earth region of the Russian Federation. The first obtained results of these studies are promising in terms of rational use of renewable energy resources in Russia. Acknowledgements: The authors would like to thank their colleagues from the Russian Research Institute of Forest Genetics, Selection and Biotechnology for their assistance in the establishment of experimental facilities. The authors would like to express their special gratitude to the workers of production enterprises of Lipetsk and Voronezh regions: Kulikovsky Forestry (Director – A.A. Sergeev), LLC "United Nurseries" (General Director – A.N. Tseplyaev), as well as a branch of LLC "Sokolinye Sady" (Director – K.P. Kolesnik). These and other production enterprises provided assistance in growing hybrids, planting variety testing and collection-mat plantations of poplars, their care and protection. For citation: Tsarev A.P., Tsareva R.P., Tsarev V.A., Evlakov P.M. Bioenergetic and Reproductive Plantations of True Poplars Species in the Central Black Earth Region of Russia. Lesnoy Zhurnal = Russian Forestry Journal, 2023, no. 5, pp. 75–89. (In Russ.). https://doi.org/10.37482/0536-1036-2023-5-75-89